(untitled) (Medicine Today, 2014)
A cross-sectional, descriptive type of study was designed to find out the difference in weight of the ovary of Bangladeshi women in relation to age and to compare with the previous studies. This study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from January to December 2009. The study was performed on 140 post mortem human ovaries collected from 70 unclaimed female dead bodies which were in the morgue under examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. The samples were divided into three age-groups including group A (10-13 years), group B (14-45 years) & group C (46-52 years) and the weight of the ovaries were measured and recorded. The difference in mean weight between the right ovary and the left ovary was statistically significant in all age group (P <0.001). The difference in mean weight of the ovary between group A & group B, group A & group C and group B & group C were statistically significant (P <0.001) DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21304 Medicine Today 2014 Vol.26(1): 12-14